Estudo ergonômico no processo produtivo na construção civil na atividade de reboco externo - Stradioto, Juliano Prado (2019)
The construction sector is the main responsible for the generation of jobs in the country, but it is also one of the leading areas in activities that require repetitive work, especially in the upper limbs, which results in an increasing number of injuries by Repetitive Stress (RSI) or Work-Related Osteomuscular Disorders (DORS). The activity chosen for the ergonomic analysis was the practice of external plastering performed on building facades, due to its high degree of difficulty and its novelty. The prevention and reduction of ergonomic risk can be achieved through the awareness of the construction companies, but also by the application of management measures and the diagnosis of risk situations in the workplace. Through the use of ergonomic tools, they perform the evaluation of the main risks for the occurrence of work-related musculoskeletal diseases. The present work used as an ergonomic analysis method, the OCRA checklist method, thus enabling an ergonomic risk analysis of the external plaster activity, which is indicated by ISO 11228-3: 2009 as the preferred process of repetitive action analysis. The data collection took place in construction sites in the cities of Ponta Grossa / PR and Porto Alegre / RS through the application of filming and interview. This research has as general objective to analyze the risk factors of biomechanical overload that influence in the aggravation of DORTs, in the activity of external plaster in building façades. The demand analysis confirmed the higher incidence of pain and lesions in the upper limbs, as well as the question of repetitiveness in the analyzed activity. The study of the chosen activity resulted in a high level of risk with the need for immediate intervention, with subsequent proposals for improvements and verification by means of recalculation of ergonomic risk. It resulted in a reduction of ergonomic risks by more than 50%, with improvements in postures and strength. The proposals for improvements and reduction of risk will enable a better quality of life for the worker, as well as a better understanding of the importance of Ergonomics for the construction sector.